2018
DOI: 10.1016/j.neuron.2018.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Subtype Diversification and Synaptic Specificity of Stem Cell-Derived Spinal Interneurons

Abstract: SUMMARY Neuronal diversification is a fundamental step in the construction of functional neural circuits, but how neurons generated from single progenitor domains acquire diverse subtype identities remains poorly understood. Here we developed an embryonic stem cell (ESC)-based system to model subtype diversification of V1 interneurons, a class of spinal neurons comprising four clades collectively containing dozens of molecularly distinct neuronal subtypes. We demonstrate that V1 subtype diversity can be modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 95 publications
1
21
0
Order By: Relevance
“…For example, the RA-synthesizing enzyme Aldh1a2 is downregulated in somites around E10 (Niederreither et al, 1997), which temporally coincides with the point at which neurons switch from expressing Onecut family members to expressing Pou2f2 and Zfhx2-4. Consistent with this idea, RA has been shown to promote Renshaw cell identity over other V1 fates and LMC identity in MNs (Hoang et al, 2018;Sockanathan and Jessell, 1998), and both Renshaw neurons and LMC neurons are neuronal subtypes that specifically depend on Onecut TFs for their generation (Roy et al, 2012;Stam et al, 2012). Conversely, later neuronal identities may be favoured by signalling pathways that are involved in progenitor maintenance and promote gliogenesis (outlined above).…”
Section: Further Diversification Of Neuronal Identitymentioning
confidence: 74%
See 2 more Smart Citations
“…For example, the RA-synthesizing enzyme Aldh1a2 is downregulated in somites around E10 (Niederreither et al, 1997), which temporally coincides with the point at which neurons switch from expressing Onecut family members to expressing Pou2f2 and Zfhx2-4. Consistent with this idea, RA has been shown to promote Renshaw cell identity over other V1 fates and LMC identity in MNs (Hoang et al, 2018;Sockanathan and Jessell, 1998), and both Renshaw neurons and LMC neurons are neuronal subtypes that specifically depend on Onecut TFs for their generation (Roy et al, 2012;Stam et al, 2012). Conversely, later neuronal identities may be favoured by signalling pathways that are involved in progenitor maintenance and promote gliogenesis (outlined above).…”
Section: Further Diversification Of Neuronal Identitymentioning
confidence: 74%
“…Thus, Notch-dependent cell-cell interactions sequentially subdivide the V2 lineage. Similarly, Notch signalling has been implicated in regulating the fate of excitatory and inhibitory neurons in the dorsal spinal cord at later developmental stages (Mizuguchi et al, 2006), the columnar identity of MNs (Tan et al, 2016), and V1 interneuron subtype formation (Hoang et al, 2018).…”
Section: Further Diversification Of Neuronal Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…For this analysis, we generated a new ESC line that expresses tdTomato in dorsal spinal inhibitory interneurons derived from Ptf1a-expressing progenitors. 45 Following differentiation of this cell line under conditions that promote the specification of dorsal interneuron identity, tdTomato-expressing interneurons were co-cultured with GFP-expressing stem cell-derived motor neurons of spinal identity ( Figures 1H and 1I). Quantification of RFP-versus GFP-positive neurons revealed that CPA treatment reduced dorsal spinal interneuron survival by only $17%, compared to a $70% decrease in the survival of co-cultured motor neurons.…”
Section: A Screen For Stressors Inducing Preferential Degeneration Ofmentioning
confidence: 99%
“…Extrinsic signals may contribute to the temporal stratification of neuronal subtypes. Recent in vitro work suggested that retinoic acid promotes Renshaw cell identity in V1 neurons (Hoang et al, 2018), and the timepoint of their generation correlates with expression of the RA-synthesizing enzyme Aldh1a2 in the adjacent somites (Niederreither et al, 1997). Thus, besides promoting neurogenesis (Novitch et al, 2003), somite-derived RA may be a determinant for early Onecut-positive neuronal subtypes.…”
Section: Temporal Specification Of Neuronal Subtype Identitymentioning
confidence: 99%